(3GdJfbjM aj CUhd Gdabgs - (3YHjO Gddg Hf eSYhO Hf eMehO Hf CMeO GdeMHhHj GdHNGQj GdMfaj, UOQ GdTQjYIs ((3Ydi Hf eMeO Hf CMeO Hf Ydi Hf jMji GdHcQi s)
(3ChdgG (B:s
(3Edjg jUYO Gdcde GdWjH hHYO , aEf GdYHO GdeJhSd Edi Gddg JYGdi HCbhi GdPQjYI YHO Gddg Hf eSYhO jbhd deG QCjJ aMUhd GdYdeAG ecHjf ai cd YgO hReGf Ydi eHGMKI CUhd Gdabg s
(3BNQgG (B:s
(3hMceg Mce CNhjg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3cJHJ GdYfhGfGJ HNW eLhOs
(3cJH HYVgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3Gdabg GdESdGejs